Age‐associated outcomes after survived out‐of‐hospital cardiac arrest and subsequent target temperature management. Issue 8 (17th June 2019) - Pätz, Toni; Stelzig, Katharina; Pfeifer, Rüdiger; Pittl, Undine; Thiele, Holger; Busch, Hans-Jörg; Reinhard, Iris; Wolfrum, Sebastian
Abstract : Background: The registry of the German Society of Intensive Care and Emergency Medicine was founded to analyze outcome of modern post‐resuscitation care. Methods: A total of 902 patients were analyzed in this retrospective, multicenter, and population‐based observational trial on individuals suffering from out‐of‐hospital cardiac arrest. All patients had return of spontaneous circulation (ROSC) and received TTM after admitted to an intensive care unit. Outcome was focused on age and analyzed by creating 4 subgroups (<65, 65‐74, 75‐84, ≥85 years). Twenty‐eight day and 180‐day survival and a favorable neurological outcome according to the Cerebral Performance Category scale were evaluated as clinical endpoints. Results: At 28‐day and 180‐day follow‐up, 44.8% and 53.4% of all patients had died, respectively. The evaluation of survival rate by age category revealed a higher mortality, but not an unfavorable neurological prognosis with increasing age. In multiple stepwise regressions, age, time to ROSC, bystander resuscitation, and cardiac cause of cardiac arrest were associated with increased chance of 180‐day survival and, in addition, bystander resuscitation, time of hypoxia, and a defibrillation performed by emergency medical service were associated with a favorable neurological outcome at 180‐day follow‐up. Conclusion: Increasing age was associated with a higher mortality, but not with an unfavorable neurological outcome. The majority of survivors had a favorable neurologic outcome 6 months after cardiac arrest.